PERSEPSI MASYARAKAT PETANI TERHADAP HUTAN DI DESA TUMANI SELATAN KECAMATAN MAESAAN KABUPATEN MINAHASA SELATAN PROPINSI SULAWESI UTARA (PERCEPTION OF FARMER COMMUNITY TOWARDS THE FOREST IN SOUTH TUMANI VILLAGE MAESAAN SUB-DISTRICT OF SOUTH MINAHASA DISTRICT NORTH SULAWESI PROVINCE) - Ricky Rexi Langoy; Martha Mareyke Sendow; Olly Esry Harryani Laoh (AGRI-SOSIOEKONOMI, 2021)
South Tumani village is a village located in The District Maesaan South Minahasa Regency, the majority of the people work as farmers. South Tumani village has a limited production forest area of 500 hectares (Ha). Based on observations made by researchers showed that people's behavior in the utilization of forest resources that are not controlled can trigger forest destruction. The purpose of this research is to find out the perception of farmers' perception of forests in The Village of South Tumani Maesaan District. For three months from August to October 2020, the data types used were primary data and secondary data obtained from interviews using questionnaires. Sampling method is done purposive sampling (determined intentionally).In accordance with the results of research on farmers' perception of forests in South Tumani Village. (1) Farmers in South Tumani Village know about the existence of forests in the eastern part of Tumani village and the types of crops in the forest. (2) Farmers know that forest resources are useful and have utilized forest resources. (3) Farmers know about the impact of forest damage and how to protect forests. (4) People are hesitant about the rules of forest protection.Â